Alternative methods to animal studies for the evaluation of topical/transdermal drug delivery systems - Junqueira Garcia, M.; de Vasconcellos, F.; Raffier, C.; Roberts, M.; Grice, J.; Benson, Heather; Leite-Silva, V. (2018)
It is critical to develop an effective understanding of the interaction between the drug, delivery system and skin in order to predict and assess skin penetration and permeation. Experimental models for the assessment of topical and transdermal delivery systems must permit evaluation of these complex interactions. Whilst in the past, animal models were commonly used, recent regulatory guidelines, based on 3R principles (refinement, reduction, replacement), encourage the rational use of animals. Alternative methods have been proposed for use in the development of topical and transdermal delivery systems which are often used in combination. We will review the current state of the art in alternative methods for topical and transdermal delivery systems development, including technologies that can assist in the characterization of skin penetration/permeation studies.